Identifying the Sources and Sinks of CDOM/FDOM across the Mauritanian Shelf and Their Potential Role in the Decomposition of Superoxide (O2-) - Heller, Maija I.; Wuttig, Kathrin; Croot, Peter L. (Frontiers in Marine Science, 2016)
Superoxide (O2-) is a short lived reactive oxygen species (ROS) formed in seawater by photochemical or biological sources, it is important in the redox cycling of trace elements and organic matter in the ocean. The photoproduction of O2- is now thought to involve reactions between O2 and reactive reducing (radical) intermediates formed from dissolved organic matter (DOM) via intramolecular reactions between excited singlet state donors and ground-state acceptors (Zhang et al., 2012). In seawater the main pathways identified for the decomposition of O2- into H2O2 and O2, involve reactions with Cu, Mn, and DOM. In productive regions of the ocean, the reaction between DOM and O2- can be a significant sink for O2-. Thus, DOM is a key component of both the formation and decomposition of O2- and formation of H2O2. In the present work we examined the relationships between O2- decay rates and parameters associated with chromophoric dissolved organic matter (CDOM) and fluorescent dissolved organic matter (FDOM) by using the thermal O2- source SOTS-1. Filtered samples (0.2 μm) were run both in the presence, and absence, of the metal chelator diethylenetriaminepentaacetic acid (DTPA) to determine the contribution from DOM. Samples were collected along a transect across the continental shelf of the Mauritanian continental shelf during a period of upwelling. In this region we found that reactions with DOM, are a significant sink for O2- in the Mauritanian Upwelling, constituting on average 58 ± 13% of the O2- loss rates. Superoxide reactivity with organic matter showed no clear correlation with bulk CDOM or FDOM properties (as assessed by PARAFAC analysis) suggesting that future work should concentrate at the functional group level to clearly elucidate which molecular species are involved as bulk properties represent a wide spread of chemical moieties with different O2- reactivities. Analysis of FDOM parameters indicates that many of the markers used previously for terrestrial sources of DOM and FDOM are called into question as marine sources exist. In particular recent work (Rico et al., 2013) indicates that algal species may also produce syringic, vanillic, and cinnamic acids, which had previously been ascribed solely to terrestrial vegetation.